How to Rescue the K-Pop Choreography: A Comparative Copyright Study with the United States - Hyejong, Kang (Universitas Muhammadiyah Yogyakarta, 2024)
The popularity of K-Pop has brought about the growth of Korean music industry and enriched most of the participants of the music industry. Unfortunately, choreographers who have created iconic dance moves did not receive proper appreciation, mainly due to the lack of copyright protection. This normative legal research employing both statutory and comparative approaches. The author examined the legal framework and industrial structure relating to choreographic works in South Korea and in the United States and made comparison between both jurisdictions. It is found that although choreographers in both countries are now actively seeking for protection of their copyright, nevertheless, the legal framework in the United States is more accommodative for the protection of choreographic works as compared to its Korean counterpart. Amendment of the Korean Copyright Act as well as changes in the industrial environment and custom are required to provide more adequate legal protection of choreographic works in South Korea